Recent advances in the applications of nanocellulose for sustainable development - Mohammad Mehdi Alighanbari; Firoozeh Danafar; Araam Namjoo; Asma Saeed (eXPRESS Polymer Letters, 2025)
The environmental and ecological concerns drive researchers to synthesize functional materials using components from natural resources. Nanocellulose (NC), derived from plants, marine animals, or microorganisms, is a green material attracting attention due to its abundance, biocompatibility, and biodegradability. NC’s interstice properties enable the synthesis of functional nanocomposites in forms like aerogels, foams, paper, sheets, or hollow filaments. This review briefly describes NC classification and production while comprehensively presenting its mechanical, rheological, optical, and electrical properties, offering foundational knowledge for future research. Additionally, it highlights recent developments in NC-based products across fields such as papermaking, water treatment, civil engineering, electronics, cosmetics, food, and medicine. For the first time, this paper explores recent advances in NC molecular simulation, providing insights into structure, arrangement, and interactions through molecular dynamic simulation. Finally, future prospects for NC-based applications are discussed to encourage studies addressing current challenges.